Rancang Bangun Sistem Informasi Pengakuan Pendapatan Dengan Metode Persentase Penyelesaian Pekerjaan Pada PT. Jaya Darmabakti Arthagraha - Wardhani, Hienny; Arifin, Mochammad; Setyawan, Henry Bambang (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Abstract: PT. Jaya Darmabakti Arthagraha (JDA) is a company engaged in construction services Mechanical Electrical (ME). In general the projects it undertakes a project worth more than ten billion and the project implementation period of more than one year. Current conditions, PT. Jaya Darmabakti Arthagraha is the process of recording the recognition of revenue based on the progress of projects in the company still has not done. During this time, the recording of revenues are recorded based on terms of income and expense are recorded based on exit / entry of project costs, so profit / loss is based on the actual terms of income and expenses to the project. To overcome these problems, we need an information system that generates a revenue recognition by percentage of completion method of work. From the results of information systems, will be a calculation of revenue recognition based on project progress using the percentage of completion of the work. From the test results and evaluation, has generated an information system revenue recognition percentage of completion method of work that is integrated with project planning in the company, so when planning the project has included planning of revenue recognition.